Evaluasi Kesehatan Struktur Bangunan berdasarkan Respon Dinamik Berbasiskan Data Akselerometer - Darmawan, Wan Fikri; Suryanita, Reni; Djauhari, Zulfikar (Department of Civil Engineering, Diponegoro University, 2017)
The aim of the research is to analysis the health of a simple frame structure based on accelerometer data. The research is a preliminary study which used the accelerometer data in the time history analysis of the structure. The parameters has been used in the study are the Story Damage Index (SDI), the ApproximateStory Damage Index (ASDI), the Flexibility Damage Index (MFDI), and the Park Ang Damage Index. The finite element analysis is used to identify the damage of building structures through the pushover analysis. The study has conducted the minor damage index, physical appearance to check the cracked beam andconcrete column. The damage index average is in the range 0-0.08. It can be concluded the building is still able to withstand the earthquake load. However, the building is stated in a minor damage condition after the earthquake occurred.